Konstitucinis Teismas kaip žmogaus teisių apsaugos institucija - Pūraitė-Andrikienė, Dovilė (Vilnius University Open Series, 2024)
The aim of this article is to highlight the role of the Constitutional Court in strengthening the protection and defence of the human rights in Lithuania. In order to achieve this aim, the following tasks are raised and addressed in the paper: 1) to reveal the forms in which the Constitutional Court contributes to the strengthening of the human rights protection; 2) to analyze the most important constitutional justice cases in the field of the human rights decided by the Constitutional Court and the most important principles of the official constitutional doctrine of the human rights; 3) to reveal how the Constitutional Court contributes to the protection of the human rights by examining the applications of courts and natural and legal persons.
Keywords: Konstitucinis Teismas; žmogaus teisių apsauga; žmogaus teisių gynimas; individualus konstitucinis skundas